Norwegen eröffnet spektakuläres Denkmal an die Hexenverbrennungen - Klaus Graf (Archivalia, 2011)
http://starkwhite.blogspot.com/2011/06/steilneset-witch-trial-memorial-by.html Dedicated to 91 victims of a 17th century witch hunt in Vardo, The Witches of Finnmark Memorial is a collaboration between artist Louise Bourgeois and architect Peter Zumthor. Set to open on the 23rd of June, the monument is located at Steilneset in Vardo, the place where the burning of the vast majority of the witches occurred. Siehe auch http://www.kongehuset.no/c27262/nyhet/vis.html?tid=92483 http://www.archdail.